Information technology : Book 1 - Evans, Virginia; Dooley, Jenny; Wright, Stanley (Berkshire Express Publishing, 2011)
Contents: Information technology; introduction to computing systems; inside the computer; computing devices; networking; the user inface; word processing;...
Keywords: Công nghệ thông tin